(untitled) (International Journal of Current Engineering and Technology, 2015)
The use of sandwich structure is increased rapidly in various fields which uses many applications ranging from satellite, aircraft, ships, automobile, railcars, bridge construction and many more the purpose of following review paper is to provide general introduction to sandwich structure and discussion on structural mechanics including types of loads acting, failure modes observed in sandwich construction and typical three point bending analysis of sandwich structure.